Oral contraceptives increase insulin-like growth factor binding protein-1 concentration in women with polycystic ovarian disease - Suikkari, Anne-Maria; Tiitinen, Aila; Stenman, Ulf-Håkan; Seppälä, Markku; Laatikainen, Timo (Fertility and sterility, 1991)
Insulin-like growth factor-I (IGF-I) stimulates ovarian androgen production. Insulin-like growth factor binding protein-1 (IGFBP-1) inhibits IGF actions in vitro. To investigate the effect of oral contraceptive (OC) pills, given for 3months, on serum gonadotropin, androgen, IGF-I, and IGFBP-1 concentrations, and glucose tolerance in seven women with polycystic ovarian disease (PCOD) and in five healthy control subjects. Seven women with PCOD and five healthy control subjects. An oral glucose tolerance test (OGTT) was performed before and after treatment with OC. After treatment with OC, serum luteinizing hormone, androstenedione, and free testosterone levels decreased, and sex hormone-binding globulin concentration increased in the women with PCOD as well as in the control subjects. The cumulative response of serum insulin to OGTT was larger in the women with PCOD than in the control subjects both before and after treatment. Serum IGF-I concentration, which was unchanged during OGTT, decreased from basal level of 326±70μg/L to 199±28μg/L, after treatment with OC in the women with PCOD, whereas no change was found in the control subjects (from 235±11μg/L to 226±11μg/L). Treatment with OC caused an increase of the mean basal IGFBP-1 concentration from 24±7μg/L to 73±14μg/L, in the women with PCOD. This increase was constant during the OGTT. In the control subjects, treatment with OC did not result in any significant change in IGFBP-1 concentrations (from 44±11μg/L to 61±9μg/L). The combination of decreased total IGF-I concentration and increased IGFBP-1 concentration induced by OC may decrease ovarian androgen production in PCOD.